Legal Certainty Regarding the Deletion of Land Records in Gunung Anyar Tambak - Ario Bagus Permadi (Green Publisher Indonesia, 2026)
Legal certainty in land registration constitutes a fundamental element in establishing orderly land administration and ensuring legal protection for land rights holders. The enactment of Article 76A of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 16 of 2021, which abolishes the recognition of traditional land ownership evidence such as petok, girik, pipil, and ipeda after 2026, carries significant juridical implications, particularly for areas that still rely on non-certificate land history documents. Gunung Anyar Tambak Subdistrict in Surabaya represents a region with complex land history structures that have not been systematically documented. This study aims to analyze the juridical implications of abolishing traditional land evidence on legal certainty and legal protection in land registration, as well as to examine the readiness of local administrative structures in implementing this policy. The research employs a normative legal method using statutory and conceptual approaches, supported by an analysis of land administration practices. The findings indicate that, normatively, the abolition of traditional evidence is intended to strengthen legal certainty through a certificate-based proof system; however, in practice, it may generate new legal uncertainties if not accompanied by adequate administrative readiness at the local level. Therefore, this policy requires institutional capacity strengthening, standardization of land history documentation, and equitable transitional mechanisms to ensure the effective realization of legal certainty and legal protection.